The Synergy of Emotional Intelligence and Resilience in Shaping Adult Life Satisfaction - Ayesha Bint-e-Nawaz; Aamna Bibi; Sidra Bibi (International Journal of Business and Economic Affairs, 2024)
The primary motive of this inquiry is to examine the connection between emotional competence, rigidity and quality of life throughout maturity. This study seeks to give precious insight into factor that contributes to grown- up’s good and academic success. To measure the relationship between emotional intelligence, resilience and life, data was collected from 150 virile and 150 womanish early grownup( age range 18 to 29) from educational institute from Haripur district using purposive sampling technique. The sample comported of virile ( n = 150) and womanish( n = 150). Students were inked through purposeful slice by posting a check link on emotional intelligence, brief resilience, and life satisfaction at Govt. Girls Degree College No. 2 Haripur. Correlation research design was applied to the current study. The researcher used the detail Resilience Scale, Shut Self Report Emotional Intelligence Scale and Satisfaction with life Scale for study purpose. The statistical technique applied for finding were descriptive statistic, correlation test and t- test. The findings indicate that emotional intelligence has significant negative correlation with detail resilience, and positive correlation with satisfaction with life, and. especially, female showed advanced emotional intelligence compared to males.